Intervention Under Inflation Targeting : When Could It Make Sense? - Hofman, David (IMF Working Papers; Working Paper, 2020)
We investigate the motives inflation-targeting central banks in emerging markets may have for intervening in foreign exchange markets and evaluate the case for such interventions based on the existing literature. Our findings suggest that the rationale for interventions depends on initial conditions and country-specific circumstances. The case is strongest in the presence of large currency mismatches or underdeveloped markets. While interventions can have benefits in the short-term, sustained over time they could entrench unfavorable initial conditions, though more work is needed to establish this empirically. A first effort to measure the cost of interventions to the credibility of policy frameworks suggests that the negative impact may be smaller than often assumed-at least for the set of more sophisticated inflation-targeting emerging-market central banks considered here.